Age and growth parameters of the dourado Salminus brasiliensis (Cuvier, 1816) from the river Cuiabá, Mato Grosso State, Brazil - Zuliani, Marina Soares; Ambrosio, Angela Maria; Francisco, Talitha Mayumi; Balbi, Thiago José; Okada, Edson Kiyoshi; Gomes, Luiz Carlos (Acta Scientiarum. Biological Sciences, 2016)
Age and growth parameters of Salminus brasiliensis (Curvier, 1816) from the Manso Reservoir and from the river Cuiabá are estimated by their fish scales. Sampling was performed between January and December 2006. There was a linear relationship between the standard length of the fish (cm) and the scale radius (mm) (r = 0.93). The coefficients of variation of standard mean lengths calculated for fish of the same age class were low (>19.0%), while temporal variation analysis of mean marginal increment showed that growth ring was annually formed in November, possibly related to the species’s reproductive period between November and January. The maximum number of rings was 12 for both sexes. The growth curve for length expressed by von Bertalanffy model was Sl = 69.0[1-e-0.21(t-(-0.86)] for males and Sl = 77.9[1-e-0.17(t-(-0.41)] for females. The growth curve in weight was Wt = 7334.6[1-e-0.21(t-(-0.86)]3.07 for males and Wt = 10226.8[1-e-0.17(t-(-0.41)]3.05 for females. Females attained greater length and weight than males. Since growth rate for the species was initially accelerated for both sexes, specimens attain size to start migration after the floods, avoiding predation and frequenting sites with greater food availability.